2009
DOI: 10.1111/j.1365-2591.2009.01555.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of several protocols for the application of ultrasound during the removal of cast intraradicular posts cemented with zinc phosphate cement

Abstract: A reduction in core diameter/height and intermittent ultrasonic application improved the removal of cast posts cemented with zinc phosphate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 19 publications
(43 reference statements)
2
17
0
3
Order By: Relevance
“…Furthermore, the application time in the present study was 15 seconds on each surface, totaling 1 minute of application, which is extremely important since many studies apply ultrasonic forces for longer periods, sucha as 3 to 16 minutes of vibration 25,26,27. It is known that the application of the ultrasonic tip for longer periods than 1 minute considerably increases temperature, which dissipates through the post/root interface causing several damages 16.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the application time in the present study was 15 seconds on each surface, totaling 1 minute of application, which is extremely important since many studies apply ultrasonic forces for longer periods, sucha as 3 to 16 minutes of vibration 25,26,27. It is known that the application of the ultrasonic tip for longer periods than 1 minute considerably increases temperature, which dissipates through the post/root interface causing several damages 16.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the type of device selected, other factors also influence the effectiveness of posts removal procedure: the method of ultrasonic vibration application, the use or not of cooling during the process, diameter and height of the post, tip movement type, which may be continuous or alternating, and the design of the ultrasonic tips 1,19,22,23,24,25. Several studies have reported techniques and devices that facilitate the removal of intraradicular posts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This alternative vibration increases the fragmentation of the zinc phosphate cement, thus favoring the detachment of the intraradicular posts. 17,21 The power and the frequency of the ultrasonic waves generated by the device determine the physical characteristics of the vibrations.…”
Section: Discussionmentioning
confidence: 99%
“…19 Several factors may interfere in the ultrasonic efficiency, such as the type of luting agent, length, form, diameter and type of post and post adaptation to the root canal walls. 8,17,18,20,21 The efficacy of ultrasound is related to the intensity and movement of the vibration, the manner in which the tip is applied on the core and the type of tip used. …”
Section: 16mentioning
confidence: 99%